MRI tracking/detection of bone marrow mesenchymal stromal cells transplantation for treatment of ischemic cerebral infarction. Issue 1 (28th March 2021) - Zhao, Nan; Niu, Rui‐Ze; Zhu, Yu‐Hang; Yu, Chang‐Yin
Abstract : Background: Cerebral stroke is the second leading cause of death with high mortality and morbidity worldwide, currently it lacks effective therapies to improve the prognosis. This study was aimed to explore the role of bone marrow mesenchymal stem cells (BMSCs) transplantation in the recovery of brain structure and function after ischemic cerebral infarction by magnetic resonance imaging (MRI). Methods: By applying internal carotid artery embolization, the ischemic cerebral infarction model in rats was established. MRI was performed to detect the imaging changes in the brain tissue after modeling, and the successful modeling was evidenced by the presence of obvious high‐signal infarct areas in the brain. BMSCs were then injected into the lateral ventricles of rats, and the recovery of brain tissue and function were quantitatively evaluated by T2‐weighted image (T2WI) and voxel‐based morphology (VBM) after 28 days. Results: The results showed that BMSCs were cell subsets with multiple differentiation potentials. Deficits caused by Ischemic cerebral infarction were relieved by BMSCs transplantation, including increase in damaged cerebral tissue and recovery of cerebral function. In addition, the combined imaging technology of VBM and T2WI quantitatively revealed the effectiveness of BMSCs in repairing damaged brain tissue structure and function. Conclusion: Taken together, the results revealed that the transplantation of BMSCs into the lateral ventricle was beneficial to repair the structure and function of the damaged brain tissue after ischemic cerebral infarction. Moreover, the combination of VBM and T2WI technology can detect the level of brain injury in ischemic cerebral infarction dynamically and noninvasively, and evaluate the recovery of structure and function of damaged brain tissue.